Uptake of heterologous DNA by Haemophilus influenzae. - Goodgal, S H (1984)
With the use of highly competent Haemophilus influenzae cells, it was possible to demonstrate the uptake of heterologous DNAs. However, these DNAs, as expected, were only 1% or less as effective when competing for uptake with Haemophilus DNA. Escherichia coli DNA was removed from solution by competent cells to the extent expected if all the E. coli DNA particles contained at least one uptake recognition signal. The data were consistent with a model in which there was one uptake signal per 20 X 10(6) to 30 X 10(6) daltons of E. coli DNA. Since H. influenzae DNA has many more recognition signals, approximately one per 2 X 10(6) daltons (Danner et al., Gene 77:311-318, 1980; K. Vogt and S. H. Goodgal, submitted for publication), it has been suggested that the slower rate of E. coli DNA binding and the so-called specificity of Haemophilus DNA binding are due to the number of recognition signals per molecule of DNA as well as the nature of the DNA receptor (Vogt and Goodgal, submitted for publication). The specificity of native H. influenzae DNA binding does not apply to the uptake of denatured DNA in the transforming system (low pH) for denatured DNA.